Aluminum Deoxidation Equilibrium in Molten Fe–Co Alloys - Gamutan, Jonah; Akaishi, Kosei; Sato, Takahiro; Miki, Takahiro (Nippon Tekko Kyokai/Iron and Steel Institute of Japan, 2022)
Aluminum deoxidation equilibrium of molten Fe–Co alloy was experimentally measured using a chemical equilibrium method and numerically assessed using a sub-regular solution model based on Darken’s quadratic formalism and a Redlich-Kister type polynomial at 1873 K. It was found that the degree of oxygen content reduction by Al-deoxidation decreased with increasing cobalt concentration in the alloy, peaking at around 40 to 60 mass% Co, and then improved with further increase in cobalt concentration. The following binary interaction parameters between cobalt and aluminum were derived in this study: